Evolution of mechanical properties and permeability of concrete during steam curing process. (November 2020) - Shi, Jinyan; Liu, Baoju; Wu, Xiang; Qin, Jiali; Jiang, Junyi; He, Zhihai
Abstract: Steam curing involves a complex moisture-thermal coupling process, which greatly affects the performance evolution of cement-based materials. The effects of mineral admixtures and curing ages on the hydration process, mechanical properties and permeability of concrete during the steam curing process had been studied, and the pore structure, micromorphology and interfacial transition zone (ITZ) were also determined by multi-scale image processing and scanning electron microscopy. The results show that the concrete performances are significant changed during the steam curing process, which can be divided into three stages. In the early stage, hydration products are less, the porosity is larger, and the ITZ is weaker. With the increase of the curing temperature and age, the hydration products are continuously deposited, the microstructure is denser, the mechanical properties are enhanced, and the permeability is decreased significantly. As a result, an empirical model is developed to describe the relationship between effective pore structure (multi-scale pores structure and ITZ) and gas permeability. Graphical abstract: Image 1 Highlights: Hydration process and mechanical performances of concrete during steam curing process were measured. Evolution of permeability of concrete with different cementitious components during steam curing process were discussed. Evolution model for apparent gas permeability of concrete during steam curing process was established.